Ramulus mori (Sangzhi) alkaloids improve intestinal oxidative damage and inflammation in DHEA-induced polycystic ovary syndrome rats via gut microbiota and metabolite modulation - Wang, Yanping; Jiang, Xianmei; Wu, Shuyi; Wang, Qiaohui; Zuo, Dan; Huang, Biao; Jian, Li; Yang, Yu; Cai, Yong; Wen, Xingjian; Yao, Ling; Geng, Shan (Frontiers in Pharmacology, 2026)
IntroductionIntestinal dysbiosis, characterized by reduced diversity and enrichment of pro-inflammatory taxa, is implicated in the pathogenesis of polycystic ovary syndrome (PCOS). Ramulus mori (Sangzhi) alkaloids (SZ-A), approved in China for type 2 diabetes with broad metabolic effects, remain untested as a microbiota-targeted intervention for PCOS.MethodsIn a dehydroepiandrosterone (DHEA)-induced rat model of PCOS, we evaluated the therapeutic efficacy of SZ-A and its underlying microbiota–metabolite interactions through integrated assessments of reproductive and endocrine–metabolic function, oxidative stress, inflammatory cytokines, and gut microbiota and serum metabolite profiles.ResultsRelative to SD rats, PCOS rats showed approximately 10-fold higher cystic follicle burden and a one-third reduction in corpora lutea, with serum testosterone rising from 0.12 ± 0.08 to 0.27 ± 0.08 ng/mL, total bile acids falling from 34.22 ± 5.52 to 20.63 ± 4.94 μM, and HOMA-IR significantly increased (all p < 0.05). SZ-A treatment reduced cystic follicles, restored estrous cyclicity and luteal formation, and shifted testosterone, total bile acids, and HOMA-IR toward SD levels. At the molecular level, SZ-A appears to act by remodeling gut microbiota composition and serum metabolite profiles. SZ-A significantly shifted microbial β-diversity in PCOS rats while retaining a community dominated by Bacteroidetes and Firmicutes with Lactobacillus and Treponema_2 as key genera. Untargeted metabolomics identified 13 PCOS-associated serum metabolites that were significantly reduced after SZ-A treatment (p < 0.05), highlighting fenoldopam as a putative mediator of its beneficial effects on ovarian function and metabolic homeostasis. With respect to oxidative injury, serum malondialdehyde (MDA) levels in PCOS rats were approximately twice those of the SD group, while total antioxidant capacity (T-AOC) and the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were significantly reduced (p < 0.05); treatment with SZ-A markedly attenuated these alterations (p < 0.05). Besides, it suppressed systemic inflammation by reducing interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) levels in serum and relevant tissues (p < 0.05).DiscussionCollectively, these findings indicate that SZ-A alleviates PCOS by attenuating intestinal oxidative stress and normalizing gut microbiota–metabolite interactions, and highlight fenoldopam as a potential effector, supporting SZ-A as a promising therapeutic candidate for PCOS.